CREATIVE LANDING PAGE DESIGN TO SHOW PROGRESS OF â€œ PETANI SEJAHTERA â€œ APPLICATION - Dimas Naufal Hakiki; Ari Purnomo Wahyu Wibowo (JURNAL DARMA AGUNG, 2023)
The farmers in Sukapura village have problems in distributing their harvests due to the large amount of costs in the planting process and the distribution process of their harvests. â€œPetani Sejahteraâ€ is the name of an application created to assist farmers in distributing their harvests to those who are willing to accommodate, so that the farmers' crops do not accumulate. In the â€œPetani Sejahteraâ€ application, farmers will be asked to input data from their harvests. To introduce the â€œPetani Sejahteraâ€ application, a landing page was created as the initial page for the introduction of the â€œPetani Sejahteraâ€ application as well as to show data and information that have been grouped and arranged, the data and information are the progress of the number of farmers, the number of products, the number of transactions, the number of partner, and a price list of products that have been registered to farmers who use the â€œPetani Sejahteraâ€ application. The data and information will be automatically updated on the landing page based on the database from the â€œPetani Sejahteraâ€ application. To make it easier for farmers and potential partner to access the landing page, a website-based landing page was created so that farmers and potential partner can access it using a smartphone or computer via a browser. By creating a landing page, farmers and potential partner know the data and information in the â€œPetani Sejahteraâ€ application.